Pendekatan body mind spirit sebagai solusi holistik untuk meningkatkan kualitas hidup pasien gagal ginjal kronis - Istianah, Istianah; Ramadhan, Muhammad Deri; Tohri, Tonika (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Chronic kidney disease (CKD) patients undergoing hemodialysis often experience a decreased quality of life due to physical, psychological, social, and spiritual disorders. A holistic approach such as the Body Mind Spirit (BMS) model is believed to improve patients' overall quality of life. Purpose: To determine the effect of the body mind spirit approach in improving the quality of life of chronic kidney disease (CKD) patients. Method: This study used a quasi-experimental design with a pre-post-test approach without a control group. The study sample consisted of 30 CKD patients selected using purposive sampling. The BMS model intervention was implemented for 4 weeks through education, relaxation, and spiritual support sessions. Quality of life was measured using the KDQOL-36 questionnaire before and after the intervention. Results: Most participants were male with an average age of 52 years, had been on hemodialysis for >2 years, and most (80%) had a poor quality of life. However, after the BMS intervention, their quality of life improved. There was a significant increase in patients' quality of life scores after the BMS model intervention (p < 0.05). The physical, psychological, and spiritual dimensions showed significant improvements. Conclusion: The body-mind-spirit model is effective in improving the quality of life of chronic kidney disease (CKD) patients undergoing hemodialysis. This approach can be used as a holistic surgical intervention strategy in hospitals. Keywords: Body-Mind-Spiritual; Chronic Kidney Failure; Hemodialysis; Quality of Life. Pendahuluan: Pasien gagal ginjal kronik (GGK) yang menjalani hemodialisa sering mengalami penurunan kualitas hidup akibat gangguan fisik, psikologis, sosial, dan spiritual. Pendekatan holistik seperti model Body Mind Spirit (BMS) diyakini mampu meningkatkan kualitas hidup pasien secara menyeluruh. Tujuan: Untuk mengetahui pengaruh pendekatan body mind spirit dalam meningkatkan kualitas hidup pasien gagal ginjal kronis. Metode: Penelitian ini menggunakan desain quasi-eksperimental dengan pendekatan pre-post-test tanpa kelompok kontrol. Sampel berjumlah 30 pasien GGK yang dipilih secara purposive sampling. Intervensi model BMS dilaksanakan selama 4 minggu melalui sesi edukasi, relaksasi, dan dukungan spiritual. Pengukuran kualitas hidup dilakukan menggunakan kuesioner KDQOL-36 sebelum dan sesudah intervensi. Hasil: Sebagian besar partisipan laki-laki dengan rerata usia 52 tahun, menjalani hemodialisa > 2 tahun, dan sebagian besar (80%) memiliki kualitas hidup yang buruk, sedangkan setelah diberikan intervensi BMI kualitas hidup pasien menjadi meningkat. Terdapat peningkatan signifikan skor kualitas hidup pasien setelah diberikan intervensi model BMS (p < 0.05). Dimensi fisik, psikologis, dan spiritual menunjukkan perbaikan yang bermakna. Simpulan: Model body mind spirit efektif dalam meningkatkan kualitas hidup pasien GGK yang menjalani hemodialisa. Pendekatan ini dapat dijadikan strategi intervensi keperawatan berbasis holistik di rumah sakit. Kata Kunci: Body Mind Spirit; Gagal Ginjal Kronik; Hemodialisa; Kualitas Hidup.